The research of functions and the construction of their graphs - LUPU, Ilie (Acta et Commentationes, Sciences of Education, 2023)
In the article, the algorithm of the research of elementary functions is proposed, used to solve various problems, which will contribute to the more effective acquisition of mathematics in gymnasiums and high schools.